Konflik Papua Barat dan implikasinya terhadap hubungan Australia-Indonesia / Keoh Kean Peng - Keoh, Kean Peng (2012)
As neighbouring countries, Australia and Indonesia are seen geographically close to each other, but they do not have the mutual understanding and also they are remarkably different in perception in various fields. The differences in cultural, religious, social, language and other aspects has result in negative perception of the people of both countries against one another, and this has made it difficult for bilateral relations to be on the right track. After East Timor separated from Indonesia due to intervention of Australia in 1999, the unrest in West Papua since the region joined in Indonesia in the 1960s shows the potential of the relationship between Australia-Indonesia to get worse, because Jakarta fears Canberra will take the similar approach in the East Timor crisis to separate West Papua from Indonesia. The purpose of this study is to examine Australia’s policies in West Papua conflict, and how it has an implication on the relationship with Indonesia. West Papua conflict is one of the critical issues that are preventing the Australia-Indonesia relationship going forward, as this issue touches the sovereignty of Indonesia and is regarded by Jakarta as a sensitive issue that should not be touched by other countries including Australia. Through this study, although this conflict is seen to worsen the bilateral relations in many aspects, but it also offers the prospect of cooperation between the two countries, because the West Papua that is remain under the rule of Indonesia is actually a common interest to both countries.